2010
DOI: 10.1007/978-3-642-15948-0_14
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Sparse Classifiers for Decoding Cognitive States in fMRI

Abstract: Abstract. The high dimensionality of functional magnetic resonance imaging (fMRI) data presents major challenges to fMRI pattern classification. Directly applying standard classifiers often results in overfitting, which limits the generalizability of the results. In this paper, we propose a new group of classifiers, "Generalized Sparse Classifiers" (GSC), to alleviate this overfitting problem. GSC draws upon the recognition that numerous standard classifiers can be reformulated under a regression framework, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 19 publications
0
42
0
Order By: Relevance
“…We refer to our approach as generalized sparse regularization (GSR). In contrast to [7] and [9], we show that GSR is applicable to a much broader set of sparse linear models than just the LASSO regression model. The adaptability of GSR to such a wide range of models stems from how any l 2 norm penalty can be merged into an l 2 data fitting loss through a simple augmentation trick.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…We refer to our approach as generalized sparse regularization (GSR). In contrast to [7] and [9], we show that GSR is applicable to a much broader set of sparse linear models than just the LASSO regression model. The adaptability of GSR to such a wide range of models stems from how any l 2 norm penalty can be merged into an l 2 data fitting loss through a simple augmentation trick.…”
Section: Introductionmentioning
confidence: 82%
“…Learning parsimonious models by imposing sparsity also simplifies result interpretation [1], which is of utmost importance in most medical studies. Since the advent of the least absolute shrinkage and selection operator (LASSO) regression model [1], where Tibshirani showed that penalizing the l 1 norm induces sparsity in the regression coefficients, numerous powerful variants were subsequently proposed [2][3][4][5][6][7][8][9]. Zou and Hastie, for instance, proposed the elastic net penalty [2], which retains the sparse property of LASSO but additionally encourages correlated…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations